Legal Review of Marketing Strategy Through the Concept of FOMO (Fear of Missing Out) in the Perspective of Islamic Law and Positive Law - Nuryani, Nuryani (JOURNAL OF ISLAMIC AND LAW STUDIES, 2025)
The development of digital technology has given rise to various modern marketing strategies, one of which is through the concept of FOMO (Fear of Missing Out). This strategy takes advantage of consumer concerns to encourage quick purchasing decisions. This study aims to examine marketing strategies through the concept of FOMO (Fear of Missing Out) from the perspective of Islamic law and positive law, with a normative approach through literature analysis, especially Law No. 8 of 1999 concerning Consumer Protection. The results of the study indicate that in positive law, the FOMO (Fear of Missing Out) strategy is acceptable as long as it does not mislead consumers and does not violate basic consumer rights as regulated in Articles 4, 8, and 9 of the Consumer Protection Law. Meanwhile, in Islamic law, this strategy is valid if it is based on correct information and does not contain elements of gharar (uncertainty) or tadlis (fraud). If the FOMO (Fear of Missing Out) strategy is used with information manipulation, then in addition to violating positive law, it also contradicts the principles of justice and honesty in Islam.